A Curriculum of Inclusivity: Towards a "Lived-Body" and "Lived-Experience" Curriculum in South Africa. Issue 2 (1st December 2018) - Koopman, Oscar; Koopman, Karen
Abstract: Drawing on Merleau-Ponty's "lived body" theory, we argue for a shift towards a lived-experience and body-specific curriculum in South Africa. Such a curriculum would view learning as a lived, embodied, social and culturally contextualised field. Its central aim would be to draw the learner into a plane of consciousness conducive to being awakened to the act of learning through an attitude of full attention. We specifically use the term "body-specific" to imply, as opposed to a one-size-fits-all curriculum model, one in which lived experience and the "body" form the conceptual basis on which the curriculum is built. Consequently, we reject the orthodox cognitive conception of the curriculum which views learning as a mental exercise oriented towards the acquisition of pre-designed knowledge that is "outer fixed" and "inner constructed". In contrast, we propose that learning should be outwardly constructed through lived experience and inwardly fixed (embodied) as knowledge develops against the pre-noetic background of the lived world. Underpinning this is the essentially Merleau-Pontian notion that the knowledge we hold originates from (i) our relationships with this world that are embodied in experience, and (ii) our engagements within society and culture. The "inner" and "outer" shift in learning infers a switch from pure, disciplinary, homogeneous, expert-led, supply-driven, hierarchical, peer-reviewed and almost exclusively university-based learning to experience-based, applied, problem-centred, trans-disciplinary, heterogeneous, hybrid, demand-driven learning. In such a curriculum, the role of the teacher would be to focus on how the world arranges itself around the learner and to guide learners to see how the world reveals itself to them through their personal lived experience.